Government Size and Growth: A Survey and Interpretation of the Evidence - Andreas Bergh; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2011)
The literature on the relationship between the size of government and economic growth is full of seemingly contradictory findings. This conflict is largely explained by variations in definitions and the countries studied. An alternative approachof limiting the focus to studies of the relationship in rich countries, measuring government size as total taxes or total expenditure relative to GDP and relying on panel data estimations with variation over timereveals a more consistent picture. The most recent studies find a significant negative correlation: An increase in government size by 10 percentage points is associated with a 0.5 to 1 percent lower annual growth rate. We discuss efforts to make sense of this correlation, and note several pitfalls involved in giving it a causal interpretation. Against this background, we discuss two explanations of why several countries with high taxes seem able to enjoy above average growth: (i) that countries with higher social trust levels are able to develop larger government sectors without harming the economy, and (ii) that countries with large governments compensate for high taxes and spending by implementing market-friendly policies in other areas. Both explanations are supported by current research.
Keywords: E62; H11; H20; O23; O43; 330; Government size; Government expenditure; Economic growth; Economic freedom; Globalization; Taxation; Cross-country regressions; Staatsquote; Wirtschaftswachstum